Chromatin extracellular trap release in rainbow trout, Oncorhynchus mykiss (Walbaum, 1792) - Van, Andre P; Alvarez de Haro, Neila; Bron, James E; Desbois, Andrew P (Fish & Shellfish Immunology, 2020)
Neutrophils release nuclear chromatin decorated with antimicrobial proteins into the extracellular milieu as an innate immune defence mechanism to counter invading microbes. These chromatin structures, called extracellular traps (ETs) and released by a process called NETosis, have been detected in mammals, certain invertebrates and some fish species, including fathead minnow, zebrafish, common carp, turbot, sole and barramundi. However, there have been no previous studies of ETs in the Salmonidae. ETs are released in response to chemical and biological stimuli, but observations from different fish species are inconsistent, particularly regarding the potency of various inducers and inhibitors. Thus, this present study aimed to describe ET release in a salmonid (rainbow trout, Oncorhynchus mykiss (Walbaum, 1792)) and uncover the inducers and inhibitors that can control this response. Highly enriched suspensions of polymorphonuclear cells (PMNs; mainly neutrophils) were prepared from head kidney tissues by a triple-layer Percoll gradient technique. ET structures were visualised in PMN-enriched suspensions through staining of the chromatin with nucleic acid-specific dyes and immunocytochemical probing of characteristic proteins expected to decorate the structure. ET release was quantified after incubation with inducers and inhibitors known to affect this response in other organisms. Structures resembling ETs stained positively with SYTOX Green (a stain specific for nucleic acid) while immunocytochemistry was used to detect neutrophil elastase, myeloperoxidase and H2A histone in the structures, which are diagnostic proteinaceous markers of ETs. Consistent with other studies on mammals and some fish species, calcium ionophore and flagellin were potent inducers of ETs, while cytochalasin D inhibited NETosis. Phorbol 12-myristate 13-acetate (PMA), used commonly to induce ETs, exerted only weak stimulatory activity, while heat-killed bacteria and lipopolysaccharide did not induce ET release. Unexpectedly, the ...